Cameroon : Fourth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, Request for Waiver of Performance Criterion, and Financing Assurances Review; Staff Report; Staff Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Cameroon. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
Cameroonian monetary developments in the first half of 2007 continued to be driven by high oil prices while inflation declined. Fiscal performance in the first half of 2007 was broadly satisfactory, although concerns about investment execution remain. Performance under the Poverty Reduction and Growth Facility (PRGF)-supported program over January-June 2007 was mixed, but corrective actions have been taken. The medium-term fiscal strategy aims at expanding priority spending while preserving macroeconomic sustainability. The authorities agreed that non-oil revenue mobilization remained key to ensuring fiscal sustainability.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet